DIGITAL TECHNOLOGIES: ‘USE OF DIGITAL MEDIA AS A METHODOLOGICAL TOOL IN HISTORY TEACHING’ - Francisca de Jesus Cangirana, Sandra; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
This article is the result of bibliographic research carried out with the aim of knowing the digital technologies applied as a methodological tool in the teaching of history, therefore understanding the paths and challenges encountered in the current scenario of Brazilian education. The methodology adopted in the research is based on dialectical historical materialism, which focuses on the essence and concreteness of the object to be researched. Thus, we sought theoretical references that dialogue with the theme, among them: Simões (2002), Tajra (2000), Morais (2008), Schmidt (2004), Tardif (1998), Marx (2007), Kenski (2003) ) between others. Given this, one can count on a diverse universe of communication technologies. From the point of view that education has developed significantly in historical terms, presenting itself more open to changes in habits, values, customs and worldview present in society.